A Retrospective Multicentric Study of Ewing Sarcoma Family of Tumors in Patients Older Than 50: Management and Outcome. Issue 1 (December 2017) - Rochefort, Pauline; Italiano, Antoine; Laurence, Valérie; Penel, Nicolas; Lardy-Cleaud, Audrey; Mir, Olivier; Chevreau, Christine; Bertucci, Francois; Bompas, Emmanuelle; Chaigneau, Loic; Levy, Dominique; Ryckewaert, Thomas; et al.
Abstract Ewing's sarcoma family of tumors (EFTs) is a group of rare and aggressive tumors. Data on EFTs in patients (pts) ≥ 50 years are limited and these pts are often not eligible for clinical trials. Some, but not all, studies have reported inferior outcome for older pts with EFTs. We conducted an IRB-approved retrospective analysis among centers of the French Sarcoma Group on pts diagnosed with EFTs at age ≥50 between 2000 and 2012. Clinical features, treatment modality and outcomes were analyzed. Seventy-seven pts were identified, including 36 females (46.8%) and the median age at diagnosis was 56 years (range: 50–86). The primary tumor was located in soft tissue in 59 pts (76.6%). Fifty-six pts (72.7%) had localized disease, among them 49 (87.5%) received chemotherapy in addition to local therapy. Their estimated 3-yr OS and event-free survival (EFS) rates were respectively 73.3% and 62.2%. Recurrence occurred in 43 pts. The estimated 3-yr OS rate was 37% in pts with metastatic disease at presentation. EFTs in pts ≥50 years are more likely to originate from soft tissue and their outcomes appear to be worse than that of younger pts treated with modern protocols.